Strategy of Cross border E-commerce Platform Operation Model – Case study of Tmall Global - Gong, Haoxun; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
With the rapid development of information technology and the increasingly obvious trend of economic globalization, cross-border e-commerce has developed rapidly against the background of the rapid development of e-commerce worldwide and with the support from all parties. Tmall Global under Alibaba Group is the most representative case currently. The operation model of cross-border e-commerce in China is still in the exploratory stage. This paper takes Tmall Global under Alibaba Group as an example to study the operation model and optimization strategies of cross-border e-commerce in China. Firstly, it outlines the relevant research and theories on operation models, as well as the operation models and innovative elements of cross-border e-commerce enterprises. Secondly, based on the discussion of China's cross-border e-commerce operation model and innovation, it analyzes the constituent elements of the cross-border e-commerce operation model. Then, through comparative analysis of the advantages and disadvantages of Tmall Global's and Amazon's, JD's and other typical domestic and foreign cross-border e-commerce operation models, it explores the optimized development enlightenment of cross-border e-commerce operation models. Finally, it studies the development optimization strategies of China's cross-border e-commerce operation model, and elaborates from aspects such as customs clearance efficiency, policy system, cross-border logistics and credit system.